Developing Technology Competencies in a College of Education - Bob Algozzine; Lonnie R, Bateman; Claudia P. Flowers; John A. Gretes; C. Dane Hughes; Richard Lambert (Arizona State University, 2011)
Colleges of education across the country are implementing initiatives to promote new and more effective teaching methods grounded in information technology and the improvement of teaching skills of graduate and undergraduate students in professional education programs. The goals for participating faculty members are to integrate information technology competencies into not only the content of the courses that they teach, but also into their instructional methods of teaching. An initiative grounded in existing coursework, extant resources, and prior experience is described in this article. Working from a state-accepted list of basic and advanced instructional technology competencies, a course-by-competency matrix was articulated to support the development of instructional technology competencies among faculty and students. Faculty and student development activities to infuse technology into teaching, using existing resources and facilities, were designed, field-tested, and evaluated. The activities were modified for use in subsequent semesters as vehicles for building or extending competencies of undergraduate and graduate students preparing for professional positions as teachers, administrators, and counselors. To support continued implementation and improvement, practical, hands-on experiences were supervised by information technology specialists, knowledgeable faculty members, and graduate students with demonstrated competence. A team of professionals with expertise in instructional technology monitors all faculty and student development activities. The effort provides a comprehensive, practical model for addressing the growing need for altering instructional methods to accommodate technology innovations for school personnel in meaningful ways.